Caring to the end: exploring the family lives of young people with a parent at the end of life - Turner, Nicola (2016)
This thesis reports on an in-depth, qualitative study of the family lives of young people with a parent at the end of life. Family is an important concept in end of life care; the support and comfort of family members is thought to be valued by people at the end of life, and the presence of family is widely understood as essential to a ‘good death’. However, attempts to interrogate what is meant by ‘family’ in these circumstances have been limited. Research studies in psycho-oncology and health sciences have tended to substitute one adult as a proxy for family. Consequently, little is known about young people’s experiences of living with dying.